Vertical Distribution, Parallel Trade, and Price Divergence in Integrated Markets - Mattias Ganslandt; Keith E. Maskus (The Research Institute of Industrial Economics (IUI), 2005)
We develop a model of vertical pricing in which an original manufacturer sets wholesale prices in two markets that are integrated at the distributor level by parallel imports (PI). The manufacturing firm needs to set these two prices to balance three competing interests: restricting competition in the PI-recipient market, avoiding resource wastes due to actual trade, and reducing the double-markup problem in the PI-source nation. These trade-offs imply the counterintuitive result that both wholesale and retail prices could diverge as a result of declining trading costs, even as the volume of PI increases. Thus, in some circumstances it may be misleading to think of PI as an unambiguous force for price integration.
Keywords: F12; F15; 330; Vertical Restraints; Parallel Imports; Market Integration; Immaterialgüterrechte; Preisdifferenzierung; Marktintegration; Außenhandel; Grauer Markt